Visual acuity in northern China in an urban and rural population: the Beijing Eye Study. Issue 9 (19th August 2005) - Xu, L; Li, J; Cui, T; Hu, A; Zheng, Y; Li, Y; Sun, B; Ma, B; Jonas, J B
Abstract : Aim: To evaluate prevalence and demographic associations of visual impairment in an urban and rural population in northern China. Methods: In the Beijing Eye Study, a population based cohort study in northern China, visual acuity was assessed for 8876 eyes (4438 subjects) according to a response rate of 83.4%. The study was divided into a rural part (1972 subjects) and an urban part (n = 2466). Mean age was 56.20 (SD 10.59) years (median 56 years; range 40–101 years). Results: Mean uncorrected visual acuity measured 0.72 (0.32) (median, 0.80), and mean best corrected visual acuity measured 0.91 (0.21) (median, 1.0). In a multiple regression analysis, best corrected visual acuity was significantly correlated with age (p<0.001), degree of nuclear cataract (p<0.001), amount of cortical cataract (p = 0.014), amount of subcapsular cataract (p<0.001), educational background (p<0.001), and refractive error (p<0.001). Rural region versus urban region (p = 0.34) and sex (p = 0.053) were not statistically significantly associated with best corrected visual acuity. Conclusions: In northern China, determinants of a low degree of best corrected visual acuity are age, cataract, low educational background, and myopia. Despite marked differences in educational background and family income, sex, and rural area versus urban area are not markedly associated with best corrected visual acuity.